Apiculture and food safety - Verde, Mayda M. (Cuban Journal of Agricultural Science, 2014)
Considering that the beekeeping sector faces important productive challenges, caused by the anthropic effect on the ecosystem and the climate change, there is a need of policies that visualize this sector as an important branch to be taken into account when designing the environmental, commercial, educative and social strategies and the ones for productive development. It is stated the bond between apiculture and the objectives of the feed production according to quantity, quality, innocuity, traceability, and sustainability, necessary for reaching the food safety and sovereignty aspired by the peoples. Subjects related to the development of the ecosystems, the bees, the apiculture within the agricultural and livestock context, the food safety and the apiculture in general are analyzed. The strengths of the Cuban beekeeping sector are stated, connected to the national food safety and sovereignty. It can be concluded that apiculture takes a part in food safety due to the important role of bees in pollination and the nutritional value of their productions. Cuba has strengths that assure this condition on the commercialized productions.